Open Source Interactive Electromagnetic Modelling - Pethick, Andrew; Harris, Brett (CSIRO, 2012)
The marine controlled source electromagnetic method has developed during the last decade for direct hydrocarbon indication. Marine controlled source electromagnetic software is still in its infancy with only a small number of open source algorithms and even fewer integrated software environments. We have developed an open source software package to encourage the development and use of the marine controlled source electromagnetic method in both industry and educational institutions. The software was written in Java and was made to perform interactive real-time synthetic modeling for varying earth models or survey parameters.